Hybrid Design of Non-Regular Linear Arrays With Accurate Control of the Pattern Sidelobes - Sartori, D.; Oliveri, G.; Manica, L.; Massa, A. (IEEE transactions on antennas and propagation, 2013)
The hybridization of an analytical thinning technique based on almost difference sets (ADSs) and a convex programming (CP) strategy is proposed for designing non-regular linear arrays over a half-wavelength lattice that fit arbitrary upper bounds on the far-field pattern. The proposed approach combines the efficiency of the ADS procedure in defining a low-sidelobe thinned arrangement with the effectiveness of the CP approach in deducing the optimal tapering to control the beam shape. A set of numerical results is presented to assess features and potentialities of the ADS-CP method.